1998
DOI: 10.1007/bf01682165
|View full text |Cite
|
Sign up to set email alerts
|

Endarteritis and mycotic aortic aneurysm caused by an oral strain ofActinobacillus actinomycetemcomitans

Abstract: Actinobacillus actinomycetemcomitans was isolated from blood cultures of a 33-year-old febrile patient with a previously undiagnosed coarctation of the aorta. Subgingival samples from diseased periodontal pockets revealed the presence of A. actinomycetemcomitans. An infected (mycotic) aortic aneurysm and endarteritis were diagnosed and surgically treated. The identity of blood and oral clinical isolates of A. actinomycetemcomitans was supported by genetic analysis, including fingerprinting by restriction fragm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…However, only a few authors have confirmed the simultaneous presence of A. actinomycetemcomitans in the periodontium and vascular walls [7,8]. Martin et al [53] reported the presence of the DNA of A. actinomycetemcomitans (the gene sequence encoding leukotoxin), originating from the oral cavity in an aortic aneurysm wall.…”
Section: Plos Onementioning
confidence: 99%
“…However, only a few authors have confirmed the simultaneous presence of A. actinomycetemcomitans in the periodontium and vascular walls [7,8]. Martin et al [53] reported the presence of the DNA of A. actinomycetemcomitans (the gene sequence encoding leukotoxin), originating from the oral cavity in an aortic aneurysm wall.…”
Section: Plos Onementioning
confidence: 99%